Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.jand.2019.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Position of the Academy of Nutrition and Dietetics: Nutrition Informatics

Abstract: It is the position of the Academy of Nutrition and Dietetics that nutrition informatics is a rapidly evolving area of practice for registered dietitian nutritionists and nutrition and dietetic technicians, registered; and that the knowledge and skills inherent to nutrition informatics permeate all areas of the dietetics profession. Further, nutrition and dietetics practitioners must continually learn and update their informatics knowledge and skills to remain at the forefront of nutrition practice. Nutrition i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Moreover, to our knowledge, there is a limited number of online digital nutrition assessment tools that accurately measure the overall nutritional situation in terms of individual or household food security during crises and the need for such a tool has been highlighted in many publications and systematic reviews [9][10][11]. The combination among the field of information technology, information sciences and nutrition has led to the generation of the concept to nutrition informatics [12]. This branch has become a novel approach for public health nutrition practitioners to practice in this field and make a profit for the health care [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, to our knowledge, there is a limited number of online digital nutrition assessment tools that accurately measure the overall nutritional situation in terms of individual or household food security during crises and the need for such a tool has been highlighted in many publications and systematic reviews [9][10][11]. The combination among the field of information technology, information sciences and nutrition has led to the generation of the concept to nutrition informatics [12]. This branch has become a novel approach for public health nutrition practitioners to practice in this field and make a profit for the health care [12].…”
mentioning
confidence: 99%
“…The combination among the field of information technology, information sciences and nutrition has led to the generation of the concept to nutrition informatics [12]. This branch has become a novel approach for public health nutrition practitioners to practice in this field and make a profit for the health care [12]. According to the international telecommunication union report, published in 2020, an estimated 90% of the population had access to a mobile-broadband network (3G or above) and 4.1 billion people used the Internet in 2019, indicating a 5.3% increase compared to 2018.…”
mentioning
confidence: 99%
“…Data linkage leads to better health outcomes through system efficiencies 39 . The Academy of Nutrition and Dietetics called for dietitians ‘to manage nutrition data in combination with standards, processes and technology to improve knowledge and practice, ultimately leading to improved quality of health care and work efficiency’ 40 . This study has shown that to achieve that vision, better tools are required and their development will require collaboration and cooperation with software manufacturers.…”
Section: Discussionmentioning
confidence: 99%
“…The present study offers a way of describing dietitian clinical judgement in the acute care setting and therefore, through language, helps let the abstract concept take form and give greater clarity. With changes being incorporated to enact and report the nutrition care process in dietetics, such as greater use of nutrition assistants ( 50 ) , informatics ( 51 ) and standardised language ( 52 ) , it is important that we consider how experienced dietitian clinical judgement is situated within the future of clinical dietetics. This may also be important from a practitioner retention and career development perspective so that we are acknowledging and harnessing the expertise that already exists to the patient’s greatest benefit.…”
Section: Discussionmentioning
confidence: 99%